Electric vehicle and power generator set coordinated frequency control method containing time variant and time lag - YU XIAODAN; MU YUNFEI; JIA HONGJIE; LI XIAOMENG; DONG CHAOYU (2017)
The invention discloses an electric vehicle cluster and power generator set coordinated frequency control method containing time variant and time lag. The method is a power system frequency modulation method by taking an electric vehicle and a power generator set as a control object on the basis that the electric vehicle participates in frequency modulation service of a system, so that the frequency problem caused by increasingly-increasing intermittent energy proportion is solved. Since the electric vehicle has the advantages of fast response speed and V2G capability, and in order to fully utilize the electric vehicle, the electric vehicle has relatively high response priority; in a coordinated control strategy, the method considers uncertainty existing in communication delay in the electric vehicle and system inertia, and an asymptotic stability new criterion capable of simultaneously processing the communication delay and the system inertia is proposed; and moreover, a group of PI controllers are employed